Investigation of the influence of various chemical substances on the field of natural damage to the cold disease of the autumn wheat. - Aliyev, Shavvoz; Musaeva, Gulbahor (Universitas Muhammadiyah Sidoarjo, 2019)
It is reported that yellow rust in the winter wheat is the most dangerous disease in the Ferghana Valley and is widespread in high humidity conditions. In recent years, the disease has spread to the irrigated grain fields of the Republic, which has significantly affected the quality and quantity of grain grown and its effective fungicidal effect.